Quantum Sensing with Cavity Optomechanical Array for Gravimetry: Optimization of Entanglement Transfer - Zeynab Faroughi; Ali Ahanj (Iranian Journal of Astronomy and Astrophysics)
‎Improvement of precision in gravimetry is an important problem in detecting the gravitational waves. In The first demonstration of using quantum optomechanical cavity in gravimetry has recently been reported. This experiment has been done by employing a cooled levitated nano-sphere as a mechanical oscillator in its ground state coupled to a cavity electrodynamics. Following this experiment, in a recent proposal, a quantum optomechanical system has been used for ‎measuring‎ of gravitational acceleration. A generic setup for gravimetry purposes, containing two couples optomechanical cavities, where mirrors play the role of oscillating parts. We study such quantum mechanical system, by investigation the dynamics of entanglement between different parts of two coupled cavity optomechanical cells. ‎For such setup, ‎optimal conditions for predesignated entanglement behavior‎, ‎based on some important parameters of the system‎, ‎like photon-photon and photon-phonon couplings‎, ‎electromagnetic field strength and mechanical mode of moving mirrors are analyzed numerically‎. We show that there exist two different behaviors for entanglement according to selected values for the system parameters. ‎‎‎